2015
DOI: 10.1210/en.2014-1032
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 Is Critical for Cartilage Development During Endochondral Ossification

Abstract: Cdc42 is a widely expressed protein that belongs to the family of Rho GTPases and controls a broad variety of signal transduction pathways in a variety of cell types. To investigate the physiological functions of Cdc42 during cartilage development, we generated chondrocyte-specific inactivated Cdc42 mutant mice (Cdc42(fl/fl); Col2-Cre). The gross morphology of mutant neonates showed shorter limbs and body as compared with the control mice (Cdc42(fl/fl)). Skeletal preparations stained with alcian blue and aliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
(37 reference statements)
3
23
0
Order By: Relevance
“…At E18.5, Cdc42 expression was exclusively restricted to hypertrophic chondrocytes and trabecular bone areas ( Figure 1a). Severe cartilage phenotypes have been reported by several previous studies (Aizawa et al 2012;Suzuki et al 2015); however, whether Cdc42 directly regulates osteogenesis still lacks solid evidence. To assess the physiological role of Cdc42 in bone formation, we genetically removed Cdc42 from the skeletal progenitors by using the Cre-loxP technique and harvested the embryos at E18.5 and E15.5.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…At E18.5, Cdc42 expression was exclusively restricted to hypertrophic chondrocytes and trabecular bone areas ( Figure 1a). Severe cartilage phenotypes have been reported by several previous studies (Aizawa et al 2012;Suzuki et al 2015); however, whether Cdc42 directly regulates osteogenesis still lacks solid evidence. To assess the physiological role of Cdc42 in bone formation, we genetically removed Cdc42 from the skeletal progenitors by using the Cre-loxP technique and harvested the embryos at E18.5 and E15.5.…”
Section: Resultsmentioning
confidence: 92%
“…Chondrocyte-specific inactivation of Cdc42 (Col2Cre;Cdc42 fl/fl ) has demonstrated that Cdc42 is essential for cartilage development during endochondral ossification (Suzuki et al 2015). To explore the underlying mechanism governing Cdc42-mediated chondrogenic differentiation, we stimulated C3H10T1/2 cells with transforming growth factor-b (TGF-b), a critical regulator in the process of chondrocyte differentiation and hypertrophy shRNA-or scramble-shRNA-expressing lentiviruses, alternatively, after cells were infected withGFP-or da-Cdc42-expressing retroviruses, cells were subjected to micromass cultures in the presence or absence of rhBMP2 at 10 ng/ml for 7 days followed by Alcian Blue staining.…”
Section: Involvement Of Cdc42 In Tgf-b-induced Sox9 Activationmentioning
confidence: 99%
See 3 more Smart Citations